2023
DOI: 10.1021/jacsau.3c00103
|View full text |Cite
|
Sign up to set email alerts
|

Enantio-Complementary Synthesis of 2-Substituted Pyrrolidines and Piperidines via Transaminase-Triggered Cyclizations

Abstract: Chiral N-heterocycles are a common motif in many active pharmaceutical ingredients; however, their synthesis often relies on the use of heavy metals. In recent years, several biocatalytic approaches have emerged to reach enantiopurity. Here, we describe the asymmetric synthesis of 2substituted pyrrolidines and piperidines, starting from commercially available ω-chloroketones by using transaminases, which has not yet been comprehensively studied. Analytical yields of up to 90% and enantiomeric excesses of up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Heckmann and Paul expanded the scope of the ATA‐triggered cyclisations to form 2‐pyrrolidines and 2‐piperidines that contain electron‐rich and electron‐deficient substituents [21] . Commercially available ω‐chloroketones, such as 57 , were aminated, triggering a spontaneous cyclisation, which caused the chlorine to act as a leaving group.…”
Section: Enzyme‐triggered Reactionsmentioning
confidence: 99%
“…Heckmann and Paul expanded the scope of the ATA‐triggered cyclisations to form 2‐pyrrolidines and 2‐piperidines that contain electron‐rich and electron‐deficient substituents [21] . Commercially available ω‐chloroketones, such as 57 , were aminated, triggering a spontaneous cyclisation, which caused the chlorine to act as a leaving group.…”
Section: Enzyme‐triggered Reactionsmentioning
confidence: 99%
“…As an additional advantage, these TA-triggered reactions are often not hindered by the challenging reaction equilibria typically associated with TA catalysed biotransformations, as the spontaneous step displaces the equilibrium towards product formation. The methodology also seems to allow for conversion of ketones with bulkier sidechains, which would not typically be accommodated well by the enzyme, such as the asymmetric TAtriggered conversion of chlorobutyrophenone 4 to pyrrolidine 6 (Scheme 1c), [5,9] and the methyl 4-oxo-4-phenylbutanoate (9 a, Scheme 2) for asymmetric lactam formation. [10] The inclusion of biocatalytic steps in asymmetric synthesis may be simplified by the availability of commercial enzymes that do not require the user to have any training in protein production and purification.…”
Section: Introductionmentioning
confidence: 99%
“…[11] We thus wished to explore how well a selection of commercially available transaminases from Codexis would accept and convert a panel of bulky ketone substrates (Scheme 2) and to examine their selectivity. The enzymes we selected for this study have been previously reported, [5,[9][10] and all include variants engineered to produce sitagliptin (2) and sacubitril.…”
Section: Introductionmentioning
confidence: 99%